Studi Etnografi Tentang Bakat Di Kalangan Remaja Di Era Digital - Abdul Hafez Assad; Resky Purnamasari Nasaruddin (Institut Agama Kristen Negeri Toraja, 2021)
This article focuses on understanding talent and action in an effort to develop talent among teenagers in the digital era, which is important as now we are in digitalization era. This article is based on data collected through the application of observational techniques and in-depth interview techniques, both of which are typical in the application of ethnographic research methods, with the object of study 20 teenagers who live in Makassar City who were selected randomly. Applying the perspective of cognitive anthropology, the results of this study show; teenagers' understanding of talent as an important thing to be developed, especially in the fields of art, technology, and skills, which is carried out through self-taught learning by relying on information, both in the form of knowledge (including experience) and news, which is available on the internet and through various media applications. social. Talent is then understood as something that is formed and/or shaped through a learning process, and not as something that is given or has been present since birth, which if developed intensively can provide benefits for the owner, or has commercial value, because talent shows are part of what is supported in the community of digital era. Artikel ini berfokus pada pemahaman tentang bakat dan tindakan untuk upaya menumbuhkembangkan bakat di kalangan remaja di era digital, yang mana hal tersebut menjadi penting sebab kini kita berada di era digitalisasi. Artikel ini berdasarkan data yang dikumpulkan melalui penerapan teknik pengamatan dan teknik wawancara mendalam, yang mana kedua teknik tersebut merupakan khas dalam penerapan metode penelitian etnografi, dengan obyek studi 20 remaja yang berdomisili di Kota Makassar yang dipilih secara acak. Menerapkan perspektif antropologi kognitif, hasil studi ini menunjukkan; pemahaman remaja tentang bakat sebagai suatu hal yang penting untuk ditumbuhkembangkan khususnya terkait bidang kesenian, teknologi, dan keterampilan, yang dilakukan melalui pembelajaran autodidak dengan mengandalkan informasi, baik berupa pengetahuan (termasuk pengalaman) maupun pemberitaan, yang tersedia di internet dan melalui ragam aplikasi media sosial. Bakat kemudian dipahami sebagai hal yang terbentuk dan/atau dibentuk melalui proses pembelajaran, dan bukan sebagai hal yang terberi atau telah terdapat sejak lahir, yang jika ditumbuhkembangkan secara intensif dapat memberikan keuntungan bagi pemiliknya, atau memiliki nilai komersial, sebab pertunjukan bakat menjadi bagian dari hal yang didukung di era digital.